ANALISIS KESESUAIAN LAHAN UNTUK RUANG TERBUKA HIJAU DAN RUANG TERBUKA BIRU DI SENTUL CITY, BOGOR - Erlinda Faradilla; . Kaswanto; Hadi Susilo Arifin (Jurnal Lanskap Indonesia, 2017)
Sentul City as a new city must be able to meet the water needs of its residents. Sentul City has annual rainfall up to 4 000 mm/year but most are rare groundwater areas. With the topography, its annual rainfall, and proximity to the river, Sentul City is a good potential to make lake and rain garden as retention pond and for replenish groundwater. An analysis of land suitability of green and blue open spaces is needed to optimizing the land use of Sentul City, especially as green and open spaces. This study was aimed to do land evaluation of green and blue open spaces in Sentul City. The research is conducted by land evaluation method using Geographic Information System (GIS). The analysis result shows that the suitable land for park was 24% of the area that moderately suitable and was 54% that marginally suitable. Land that are moderately suitable for urban forest are 25% and 75% are marginally suitable. Land that are moderately suitable for golf are 77% of the area, and 23% are marginally suitable. Land that are suitable for lake as retention pond are 11% of the area, and land that are suitable for rain garden are 22% of the area.